Attention to women in situation of intrauterine fetal death: experiences of health professionals - Taynnara Caroline Serafim; Beatriz Helena Naddaf Camilo; Mariana Rodrigues Carizani; Mariana De Gea Gervasio; Diene Monique Carlos; Natália Rejane Salim (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objectives Understand the experiences of health professionals in obstetric care in relation to the situation of intrauterine fetal death. Method Study of a qualitative approach, in which 11 health professionals participated. Data were collected through semi-open interviews and submitted to thematic content analysis. Results The professionals' difficulty in dealing with the topic and its invisibility during the training proved to be challenging. The lack of ambience and the forms of organization of attention reflected in the care for women and families who are undergoing intrauterine fetal death. The lack of strategies and spaces for sharing among professionals was directly related to the suffering and feeling of helplessness in the cases. Final considerations There is a need to develop strategies for changes in the model and organization of the service in the face of situations of fetal death, promoting spaces that are welcoming producers.